2012
DOI: 10.4304/tpls.2.10.2035-2044
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Wiki Applications in Collaborative Writing

Abstract: Wiki is increasingly gaining popularity in language learning. Some researchers suggest that wiki is a useful tool that enhances collaboration among students. Moreover, collaborative writing through wiki is an effective strategy for improving students’ writing skills. This review summarizes findings of empirical research studies on the application of wiki in collaborative writing from 2005 till 2011. Some directions for future research related to the use of wiki for collaborative writing are also suggested Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…According to Elola and Oskoz (2010) and Strobl (2015), participants engaged in both individual and collaborative writing in pairs, and they reported favorable satisfaction of computer-mediated collaborative writing (CMCW). The findings are consistent with Ansarimoghaddam and Tan (2013) research. They investigated the impact of face-to-face (f2f) interactions and computer-mediated collaborative writing (CMCW) on individual writing outcomes among thirty Malaysian English as a Second Language (ESL) participants.…”
Section: Learners' Perspectives On Computer-mediated Collaborative Wr...supporting
confidence: 91%
“…According to Elola and Oskoz (2010) and Strobl (2015), participants engaged in both individual and collaborative writing in pairs, and they reported favorable satisfaction of computer-mediated collaborative writing (CMCW). The findings are consistent with Ansarimoghaddam and Tan (2013) research. They investigated the impact of face-to-face (f2f) interactions and computer-mediated collaborative writing (CMCW) on individual writing outcomes among thirty Malaysian English as a Second Language (ESL) participants.…”
Section: Learners' Perspectives On Computer-mediated Collaborative Wr...supporting
confidence: 91%
“…Wikispaces is one of the Wiki applications in writing. It can be written and re-written multiple times by anyone, anywhere and anytime, because it offers technical core functions such as editing, links, thread changes, and search functions (Ansarimoghaddam et al, 2012;Ansarimoghaddam & Tan, 2013). The purpose of using Wikispaces is to encourage the students to discuss their argumentative essay from the beginning of the pre-writing phase till the completion of the final draft.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Although students embraced wiki-based learning but they maintained the habit of cramming to achieve high grades. Journal of Research in Curriculum, Instruction and Educational Technology Ansarimoghaddam et al (2012) found that wikis could be a useful tool for language learning. Wikis provided an interesting collaborative writing platform.…”
Section: Wikis In Language Instructionmentioning
confidence: 99%